2010
DOI: 10.1186/1471-2458-10-256
|View full text |Cite
|
Sign up to set email alerts
|

Attributable mortality to radon exposure in Galicia, Spain. Is it necessary to act in the face of this health problem?

Abstract: BackgroundRadon is the second risk factor for lung cancer after tobacco consumption and therefore it is necessary to know the burden of disease due to its exposure. The objective of this study is to estimate radon-attributable lung cancer mortality in Galicia, a high emission area located at the Northwest Spain.MethodsA prevalence-based attribution method was applied. Prevalence of tobacco use and radon exposure were obtained from a previously published study of the same area. Attributable mortality was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Studies on radon attributing to lung cancer mortality provide indirect evidence of this joint effect between tobacco and radon. Whereas attributable mortality exclusively due to radon exposure is very low, in most lung cancer deaths, smoking is present with more or less intensity (30,31). The present study has found no effect of radon exposure in never-smokers.…”
Section: Discussionmentioning
confidence: 38%
“…Studies on radon attributing to lung cancer mortality provide indirect evidence of this joint effect between tobacco and radon. Whereas attributable mortality exclusively due to radon exposure is very low, in most lung cancer deaths, smoking is present with more or less intensity (30,31). The present study has found no effect of radon exposure in never-smokers.…”
Section: Discussionmentioning
confidence: 38%
“…The attributable fraction of lung cancer caused by residential radon exposure has been estimated in several studies. In addition to the estimation by Darby et al [ 8 ] that 9 % of deaths in lung cancer in Europe is caused by radon exposure, such calculations have been reported from the USA [ 6 ], Canada [ 15 ], Germany [ 16 ], England [ 17 ], Romania [ 18 ], Spain [ 19 ], France [ 20 ], the Netherlands, and Sweden [ 21 ]. The estimated proportion of radon-caused lung cancer varied between 3 % in England and 20 % in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…A día de hoy, desconocemos la puesta en marcha de ninguno de ellos. Quizá esto se deba a que el radón no se ve ni se huele, aunque participa en torno al 10-25% de todos los casos de cáncer de pulmón 23,24 .…”
Section: Políticas De Protección Internacionales Y Nacionalesunclassified